If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 3(x + -6) Reorder the terms: 15 = 3(-6 + x) 15 = (-6 * 3 + x * 3) 15 = (-18 + 3x) Solving 15 = -18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 15 + -3x = -18 + 3x + -3x Combine like terms: 3x + -3x = 0 15 + -3x = -18 + 0 15 + -3x = -18 Add '-15' to each side of the equation. 15 + -15 + -3x = -18 + -15 Combine like terms: 15 + -15 = 0 0 + -3x = -18 + -15 -3x = -18 + -15 Combine like terms: -18 + -15 = -33 -3x = -33 Divide each side by '-3'. x = 11 Simplifying x = 11
| a=5x+7*20 | | 4v+1= | | x+x+2+x+4=-21 | | 0=3/18y+12 | | 150+2w=195-w | | 10x+15=6x+7 | | x/2+x/8=8 | | 5(y-6)=7y-30 | | 6(n-5)=66 | | -5x-6+9=-19 | | x=4(90-x)+5 | | 127-r=62 | | -3(4X-3)=-12x+13 | | -5x-6+9=19 | | 0=8/12y-40 | | 7x-2=(x+1) | | -2x-8+6=7-4x-x | | -1(h+13)=5 | | 49-5=2a-3 | | 2(x-2)=-5 | | 2+4+3x=18 | | 14-(2c+5)=-7c+29 | | 5(2x-3)-x+8=13 | | 33=528x | | 10x+10 = +9x+15 | | X+4=-2-5x | | -2(x-4)=22 | | 7+4(7+4-25)= | | 4h+1+12h=36 | | 3x+57=7x+9 | | -(8y+1)-(-7y-3)=2 | | 15-29=2(x-3) |